1968
DOI: 10.1002/jobm.19680080204
|View full text |Cite
|
Sign up to set email alerts
|

Zur Frage der biologischen Verwitterung: Einfluß der Mikroflora auf die Bausteinverwitterung und ihre Abhängigkeit von edaphischen Faktoren

Abstract: EinleitungDic Gesteinsverwitterung ist, ein Stoff-und Energieaustausch an der Grenzflache zwischen Lithosphare und Atmosphare. Die natiirliche Grenze dcr Verwitterungserscheinungen ist durch die Eindringtiefe von Losungen, Gasen und Mikroorganismen in das Gcstein tlefiniert. Der menschliche Eingriff bei der Verwendung eines Gesteins zu Bauzweclten fuhrt in vielen Fallen zu einem Wiederaufleben von Verwitterungsvorgangen, die im Aufschlun bereits z u m Erliegen gekommen sein mogen. Hierbei spielen geanderte Obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Whilst there is incontrovertible evidence of mineral disintegration, chemical modification and leaching by lithobionts, other studies have highlighted bioprotective activities, which were also hypothesized many years ago (Krumbein 1968). Such hypotheses were based on early macroscopic observations of differential erosion rates with and without lithobionts, suggesting an umbrella-like protective effect (Mottershead and Lucas 1990;Özvan et al 2015).…”
Section: Biodeteriorative And/or Bioprotective Effectsmentioning
confidence: 99%
“…Whilst there is incontrovertible evidence of mineral disintegration, chemical modification and leaching by lithobionts, other studies have highlighted bioprotective activities, which were also hypothesized many years ago (Krumbein 1968). Such hypotheses were based on early macroscopic observations of differential erosion rates with and without lithobionts, suggesting an umbrella-like protective effect (Mottershead and Lucas 1990;Özvan et al 2015).…”
Section: Biodeteriorative And/or Bioprotective Effectsmentioning
confidence: 99%
“…Several studies revealed the participation of nitrifying bacteria in rock and soil mineral weathering (Wagner and Schwartz 1965;Faurie 1977;Lebedeva et al 1978;Berthelin et al 1985). Many more studies dealt with the role of nitrifying bacteria in the biodeterioration of building stone (e.g., Krumbein 1968;Sand and Bock 1991;Bock and Sand 1993;Mansch and Bock 1998;Warscheid and Braams 2000). In these studies the focus of interest was on the aspect of deterioration and not on the process of biogenic metal mobilization.…”
Section: Introductionmentioning
confidence: 96%
“…Representatives of this group of organisms have been used to leach heavy metals from contaminated soil (Gomez and Bosecker 1999;Nareshkumar et al 2008). Sulfur-oxidizers also play an important role in the deterioration of building materials like concrete, limestone, or sandstone (e.g., Krumbein 1968;Milde et al 1983;Sand and Bock 1991;Gaylarde et al 2003).…”
Section: Introductionmentioning
confidence: 99%